A Simple Microfluidic Chip Design for Fundamental Bioseparation. (8th January 2014) - Chan, Alan S.; Danquah, Michael K.; Agyei, Dominic; Hartley, Patrick G.; Zhu, Yonggang
Abstract : A microchip pressure-driven liquid chromatographic system with a packed column has been designed and fabricated by using poly(dimethylsiloxane) (PDMS). The liquid chromatographic column was packed with mesoporous silica beads of Ia3d space group. Separation of dyes and biopolymers was carried out to verify the performance of the chip. A mixture of dyes (fluorescein and rhodamine B) and a biopolymer mixture (10 kDa Dextran and 66 kDa BSA) were separated and the fluorescence technique was employed to detect the movement of the molecules. Fluorescein molecule was a nonretained species and rhodamine B was attached onto silica surface when dye mixture in deionized water was injected into the microchannel. The retention times for dextran molecule and BSA molecule in biopolymer separation experiment were 45 s and 120 s, respectively. Retention factor was estimated to be 3.3 for dextran and 10.4 for BSA. The selectivity was 3.2 and resolution was 10.7. Good separation of dyes and biopolymers was achieved and the chip design was verified.